Trends Analysis of Ozone Hole Annual Records Using SBUV Data Version 8.6 (1979 to 2017 Datasets) - Ekhwan Toriman, Mohd; Garba Abdullahi, Musa; Khairul Amri Kamarudin, Mohd; Umar, Roslan; Muhammad Nalado, Aliyu; Firoz Khan, Md (International Journal of Engineering and Technology, 2018)
Ozone is the triatomic of oxygen forms within the Earth's atmosphere from the ultraviolet dissociation of oxygen molecules, within tropical stratosphere. It is conveyed toward the extratropics through the Brewer-Dobson circulation (BDC), generating a layer in the stratosphere known as a protective ozone layer. The data from NASA and NOAA measurements of ozone shows that the ozone layer has stopped deteriorating across the world; nonetheless no strong intensification has been detected at latitudes amongst 60Â°â€¯S and 60Â°â€¯N in the outer the Polar Regions within 60Â° to 90Â°.In this study, the evidence of the ozone hole from satellite measurements, and evidence that ozone within the lower stratosphere at the amid of 60Â°â€¯S and 60Â°â€¯N has continuous to decline after the Montreal Protocol. This study explained that, upper stratospheric ozone is improving; the recent descending trend in the lower stratosphere prevails, consequential in a descending trend in stratospheric ozone amongst 60Â°â€¯S and 60Â°â€¯N. The trend indicated that by 2060 to 2080, the ozone hole is expecting to have complete heal. Hence, the details for the continual decrease of ozone in the lower stratosphere are not clear; this study models do not prescribe these trends, and thus is a gap for another research.Â Â Â Â Â Â Â Â Â